Electrical conductivity testing of corn seeds as influenced by temperature and period of storage - Fessel, Simone Aparecida; Vieira, Roberval Daiton; da Cruz, Mara Cristina Pessoa; de Paula, Rinaldo Cesar; Panobianco, Maristela (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effects of temperature (10, 20, 30, 20/10 and 30/10ºC) and period of storage on electrical conductivity (EC) in four seed lots of corn (Zea mays L.), as well as the mineral composition of the soaking solution. EC test determines indirectly the integrity of seed membrane systems, and is used for the assessment of seed vigor, because this test detects the seed deterioration process since its early phase. The research comprised determinations of water content, germination, accelerated aging (AA), cold (CT) and EC vigor tests, and determinations of Ca2+, Mg2+ and K+ release to the solution, after seed soaking of four corn seed lots. The evaluations were performed each four months during a period of 16 months. For statistical analysis, a completely randomized split plot design was used with eight replications. Except for seed lots stored at 10ºC, all vigor evaluations revealed a decline in vigor, but AA and CT showed more sensitiveness to declines of seed physiological quality than EC. Potassium was the main leached ion regardless of the storage temperature.
Keywords: Zea mays; vigor; seed leachates; potassium